Mecanismos de regeneração natural e estrutura populacional de três espécies arbóreas em remanescente de floresta ombrófila mista, Rio Grande do Sul - Avila, Angela Luciana de (2010)
The ecology of regeneration and population dynamics is necessary information to the conservation and management of forest ecosystems. Thus, this study aimed to characterize: a) the mechanisms of natural regeneration in a Mixed Rain Forest remnant and b) the population structure of Araucaria angustifolia (Bertol.) Kuntze, Blepharocalyx salicifolius (Kunth) O. Berg and Ilex paraguariensis A. St.-Hil. Therefore, the structure of the sample project PELD/CNPq was utilized, which was installed in the National Forest of São Francisco de Paula, RS, Brazil to evaluate six clusters (1 ha), with 16 plots (20 x 20m) each, disregarding 10m surround. The mechanisms of regeneration that have been evaluated were seed rain (SR), soil seed bank (SB) and a seedling bank (SeB) (individuals ≥ 30cm in height and diameter at breast height (DBH) <1cm). Additionally, natural regeneration establishment (RNE) (1 ≤ DBH <4.8 cm) sampled in cells of 3.16 x 3.16m, the size class I (SC I) ( 4.8 ≤ DBH <9.55 cm) in plots 10 x 10m and SC II (DBH ≥ 9.55 cm) shown on 96 plots of 20 x 20m were also considered for the study of populations. These data were collected in 2008, also being measured the DBH and sociological position. The mechanisms of regeneration were evaluated for the floristic composition and horizontal structure. In addition, the cluster analysis method TWINSPAN (Two-way Indicator Species Analysis) and canonical correspondence analysis (CCA) were performed for the SeB. The population structure of the three species was examined by characterization of the sociological position, spatial distribution and frequency in size classes. In SR, we sampled 81 species, 46 genera and 28 families, in SB, 103, 65 and 41 and in SeB, 88, 57 and 36, respectively. The analysis by TWINSPAN ordered the formation of three groups in SeB, with their history of interference and environmental conditions. The CCA indicated the slope as environmental variable with the greatest influence on the distribution of plots and species. Group 1 had higher deposition of seeds, however, the lowest densities for the SB and SeB, which is correlated with a decrease in slope. The highest values in SR, SB and SeB were observed in Group 2, with the highest level of anthropogenic interference. Group 3, with lower SR and intermediate density for the other mechanisms, had its plots distributed in accordance with the increase in slope. Allophylus edulis (A. St.- Hil., Cambess & A. Juss.) Radlk., Piper xylosteoides Steud. and Piper aduncum L. showed positive correlation with the increase in slope. The population structure of the three species that were studied showed clustered distribution. Araucaria angustifolia, which is an emerging species, showed high density of individuals regenerating in environments with higher levels of alteration. Blepharocalyx salicifolius and Ilex paraguariensis, have distributed themselves predominantly in the upper and middle strata, and have shown higher population stability within the group on more advanced successional stage. Consequently, it is possible to conclude that the groups determine different patterns in forest regeneration and the structure of populations; therefore, they should be considered in case of possible interventions in the ecosystem.